Evaluation of Metformin + Sitagliptin versus Metformin + Glibenclamide on Glycemic Control in Iraqis Type 2 Diabetic Patients - M. Al-Temimi, Hassan; j.Al-Shamma, Kassim; M.Alrubaie, Salim (Iraqi Journal of Pharmaceutical Sciences, 2017)
Combination therapy with a dipeptidyl peptidase–4 inhibitor and metformin or metformin+ glibenclamide results in substantial and additive glucose- lowering effects in Iraqis patients with type 2 diabetes mellitus . This study evaluated the glycemic control by using two groups of combinations of drugs metformin + glibenclamide and metformin + sitagliptin in Baghdad teaching hospital / medical city. 68 T2DM patients and 34 normal healthy individuals as control group were enrolled in this study and categorized in to two treatment groups. The group 1 (34 patients ) received ( metformin 500 mg three times daily + glibenclamide 5 mg twice daily ) and the group 2 (34 patients) received (metformin 500 mg three times daily + sitagliptin 100 mg once daily ). From each patients 5 ml of blood was obtained by veinpuncture and the serum was separated and used for estimating plasma glucose level (FPG,PPG) and HbA1c.The mean fasting plasma glucose and postprandial plasma glucose significantly lower for group 2 patients for 3 and 6 months of treatment (129.02 ± 1.96 and 118.4 ± 1.33), (159.38 ± 4.72 and 123.88 ± 2.41 mg / dl) respectively for fasting plasma glucose and postprandial plasma glucose respectively than in group 1 patients (150.76 ± 3.97 and 127.79 ±2.52) ,(173.25 ± 7.99 respectively and 140.67 ± 4.66 mg / dl) for fasting plasma glucose (FPG) and postprandial plasma glucose (PPG) respectively. The mean HbA1c % significantly lower for group 2 patients for 3 and 6 months of treatment (6.12 ± 0.091and 5.83 ± 0.083 ) respectively compared to group 1 patients (7.1 ± 0 .63 and 6.81 ± 0.12 ). In conclusion , the combination of metformin + sitagliptin improved fasting plasma glucose , postprandial plasma glucose & HbA1c % in comparison with metformin + glibenclamide combination.Keywords : Sitagliptin, Metformin , Glibenclamide ,Type 2 Diabetic Patients.